The Filipino Dentists meeting the competencies for the 21st century professional practice - Valerio, Marie Arlene Christine T. (2025)
While society dictates the demand for healthcare, and the different dental institutions address the need to produce competent dentistry graduates, Filipino dentists must have the competencies expected of them to practice in these challenging times. Health professions education (HPEd) through continuing professional development (CPD) must address the mismatch of professional competencies to patient and population priorities. Regular attendance in CPD programs may help develop or enhance these competencies if the standards of practice and the individual dentist’s needs match. In Eliot Freidson's theory of profession, though credentialism and autonomy have been established in dental practice in the Philippines, knowledge and expertise must be described. This is an exploratory sequential mixed-method study. It presented the profiles of Filipino dentists and how their competencies meet the demands of 21st-century professional practice as they participate in CPD programs organized by the Philippine Dental Association (PDA). Competencies based on the key areas of qualifications stipulated in the Philippine Qualifications Framework (PQF) were used. Data collection was completed in three phases: face-to-face (FTF) and online. The first phase collected qualitative data through semi-structured Key Informant Interviews (KII) from five representatives of the tripartite authorities in dentistry, the PDA, the Commission on Higher Education (CHED), and the Professional Regulations Commission (PRC). The respondents were part of these agencies, as a current or former member from 2017 to 2024, when the CMO 03, s.2018 was adopted and promulgated, and during the passage of the PQF, up to the transition period of 2024. They were involved in the planning and implementation; therefore, they are the experts in reviewing the competencies and the performance indicators. The data from this interview was tabulated and used as a guide to formulate the questionnaire, which was used for quantitative data collection. The second phase used a survey with responses from 480 active PDA members. A printed questionnaire was distributed during conferences, and an online questionnaire was sent via email. Descriptive statistics were used to analyze this data. The survey results were presented in a second KII with the same respondents as the first, to describe their perceptions of the respondents' strengths and weaknesses. Data transcription and thematic analysis were done to summarize the findings. CPD programs from 2022 to 2025 were analyzed using a curriculum map. All data were then integrated. Results show that the respondents are predominantly female dentists practicing in Luzon, with a mean age of 47.6 years and an average practice time of 21.6 years. Most of these dentists perform multiple procedures, with general dentistry basic procedures being the most practiced, followed by Orthodontics, Prosthodontics, and Oral Surgery. Pediatric, Dental Public Health, and Periodontics are the least practiced. Their strength is their focus on their patients and private practice, abiding by ethics and moral principles. Their active participation in CPD programs shows their thrust for lifelong learning. Their weaknesses stem from poor research engagement, leadership, and practice management skills. Out of the 380 lectures conducted through the PDA CPD programs for the last three years, the majority are general dentistry topics introduced through a 45-minute plenary lecture and evaluated through multiple-choice questionnaires, which do not align with the course outcomes. The next most offered topics were Oral Surgery, Prosthodontics, and Periodontics. The least offered topics were Pediatrics, Endodontics, and Dental Public Health. The mapping of the competencies addressed in these programs shows that they are focused on providing quality care, communicating effectively, and practicing lifelong learning. There is poor engagement in the other eight competencies; research, leadership, and business principles are the least addressed. The CPD programs do not have outcomes-based education designs and are market-driven; therefore, they cannot respond to the general population's oral health problems. HPEd programs focused on primary healthcare, research, practice management, and leadership within the health profession are needed to prevent and eradicate the burden of oral disease.
Thesis (MHPEd)
print & pdf
Keywords: Filipino Dentists; Philippine Qualifications Framework; Health Professions Education; Competencies